Assessing Economic Efficiency in Teff Production: Evidence from Gombora Woreda, Central Ethiopia - Ababiya, Abraham; Wosenyeleh, Genene; Teshale, Shefaraw; Assefa, Kacha; Ergicho, Yisihak (International Journal of Economics and Management, 2026)
Teff is a major cereal crop extensively cultivated in Gombora Woreda of Hadiya Zone, Central Ethiopia. Despite its importance, significant disparities in productivity exist among teff-producing farmers, largely due to differences in resource use efficiency. This study aimed to assess the level of economic efficiency in teff production and to identify key sources of inefficiencies among smallholder farmers in the study area. The research was based on primary cross-sectional data collected from 185 randomly selected producers using a two-stage sampling technique. A Stochastic Frontier Model (SFM) was employed to estimate economic efficiency levels and identify influencing factors. The results revealed that the mean economic efficiency of teff producers was 41.9%, indicating that there is potential to enhance output by 58.1% through improved resource allocation and utilization under existing technological conditions. The Stochastic Frontier Production (SFP) function identified several factors that significantly influenced economic inefficiency, including education level, soil fertility, livestock ownership, farm size, off-farm income, extension contact, training, and distance to market. Notably, farm size and distance to the nearest market were found to positively and significantly impact economic inefficiency, suggesting that larger and more remote farms face greater challenges in optimizing resource use. The findings highlight a considerable scope for improving economic efficiency among teff producers through interventions aimed at enhancing both technical and allocative efficiency. Strengthening extension services, improving market access, and promoting farmer training are recommended to boost productivity and ensure sustainable teff production in the study area.